DESA SEBAGAI SUBYEK PEMBANGUNAN: STUDI DESENTRALISASI, KELEMBAGAAN, DAN PARTISIPASI WARGA - Sutisna, Agus; Wulansari, Ratu Diah; Furqon, Wahyul; Nazmudin, Nazmudin (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
This article develops a conceptual framework positioning the village as a subject of development through integrative analysis of decentralization, social institutions, and citizen participation in village governance. Unlike earlier conceptual studies that separate these elements, this study offers theoretical novelty by situating them within a mutually reinforcing causal relationship to realize village autonomy. Using a qualitative-descriptive approach, the article examines the main regulation on villages, namely Law No. 6 of 2014, as well as theoretical perspectives on decentralization, social institutions, and citizen participation. Findings reveal that delegation of authority to villages has not been fully accompanied by strengthening local institutions, developing policy literacy, and enhancing citizen participation. This article contributes to public administration and village governance studies by emphasizing that village autonomy is both institutional and social construction, rather than merely a regulatory product. The study recommends revitalizing village social institutions, strengthening citizen capacity and participation, and adopting development approaches rooted in local aspirations and community initiatives. It also opens space for further empirical research to test the effectiveness of the proposed integrative framework in practice.